Uma abordagem para evolução e reconciliação de linhas de produtos de software clonadas - Lima, Gleydson de Azevedo Ferreira (2014)
Software product line engineering promotes large software reuse by developing a system family that shares a set of developed core features, and enables the selection and customization of a set of variabilities that distinguish each software product family from the others. In order to address the time-to-market, the software industry has been using the clone-and-own technique to create and manage new software products or product lines. Despite its advantages, the clone-and-own approach brings several difficulties for the evolution and reconciliation of the software product lines, especially because of the code conflicts generated by the simultaneous evolution of the original software product line, called Source, and its cloned products, called Target. This thesis proposes an approach to evolve and reconcile cloned products based on mining software repositories and code conflict analysis techniques. The approach provides support to the identification of different kinds of code conflicts – lexical, structural and semantics – that can occur during development task integration – bug correction, enhancements and new use cases – from the original evolved software product line to the cloned product line. We have also conducted an empirical study of characterization of the code conflicts produced during the evolution and merging of two large-scale web information system product lines. The results of our study demonstrate the approach potential to automatically or semi-automatically solve several existing code conflicts thus contributing to reduce the complexity and costs of the reconciliation of cloned software product lines.